2021
DOI: 10.1021/acssuschemeng.1c02260
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Potential Applications of Nanometal Derivatives in Gaseous Bioenergy Pathways: Mechanisms, Life Cycle, and Toxicity

Abstract: Nanosized metal derivatives (NMDs), referring to metals and their oxides, are extensively utilized as additives for anaerobic digestion (AD) and dark fermentation (DF) processes, for enhancing the production of methane (CH 4 ) and hydrogen (H 2 ), respectively. NMDs-derived positive impacts were widely confirmed in many previous studies; however, no consensus exists about how these have been acquired. Undoubtedly, NMDs affect extracellular electron transfer (EET). Consequently, we explore how biotic−biotic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 229 publications
0
3
0
Order By: Relevance
“…In contrast, the discolouration during non-feeding periods (data did not showed) could be related to oxidation of Fe 2+ from magnetite delivering additional electrons for methanogenesis [ 15 ]. Furthermore, magnetite itself is a conductive mineral and has been shown to compensate for the deficiency of e-pilins, enabling probably direct electron transfer from fermenting organisms to methanogens [ 32 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the discolouration during non-feeding periods (data did not showed) could be related to oxidation of Fe 2+ from magnetite delivering additional electrons for methanogenesis [ 15 ]. Furthermore, magnetite itself is a conductive mineral and has been shown to compensate for the deficiency of e-pilins, enabling probably direct electron transfer from fermenting organisms to methanogens [ 32 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACS SCE perspectives that contain a compelling account of scientific and sustainability attributes of the reviewed topic will not only satisfy the desired quality features but also have a high probability of paving the way for future scientific and technological advances. We refer prospective authors to a sampling of recent articles, where they will gain a better understanding of the attributes of published ACS SCE perspectives.…”
Section: Beyond a Good Review: Elements Of An Acs Sce Perspectivementioning
confidence: 99%
“…Microbial activity is directly responsible for the biohydrogen generating process and is the most crucial aspect to consider. Supplementing highly conductive nanomaterials (such as graphene, graphene oxide (GO), and reduced graphene oxide (RGO)) to anaerobes has been considered a promising solution for enhancing H 2 -producing bacterial activities in the fermentation process. , Graphene has unique characteristics such as large specific surface area, high mechanical strength, high chemical stability, high biocompatibility, and excellent electrical and thermal conductivity, with a great potential to improve the stability and efficiency of fermentation. , Previous studies have shown that graphene is a strong candidate for improving bacterial proliferation and enhancing biological activity. Despite the aforementioned merits, graphene is still a prohibitively costly material for large-scale applications.…”
Section: Introductionmentioning
confidence: 99%